Deutsch als Wissenschaftssprache, where are you? Einige Bemerkungen zu den Artikelüberschriften in der deutschen Onlinepresse - Jachym, Barbara (Glottodidactica, 2014)
The role of the German language in scientific communication in Germany has long been the subject of much discussion. In the media, including online, you can find a numerous articles on the subject. Titles in the press show that the German public is very concerned about this state of affairs. The headlines already leave no illusions that the German language is displaced in the scientific research by the English language. Are we dealing with the birth of new lingua franca? Based on selected titles I tried to show how far they correspond with the content of the article. Subjected analyses allowed to discover language strategies used in the titles to illustrate the problem.